I've Got A Moonlight Date (At The Golden Gate) - Frank E. Churchill::::::::: (Paramount Music Corporation)
Piano and vocal score, 5 p. At head of title: Theme song of the Golden Gate International Exposition On cover: From the Golden Gate International Exposition On p.[2] is advertisement of The bells of Treasure Isle, the anthem of the Golden Gate International Exposition Information about the exposition and San Francisco on verso of last leaf.